Doctors Identify Hemorrhage Better during Chart Review when Assisted by Artificial Intelligence - Laursen, Martin S.; Pedersen, Jannik S.; Hansen, Rasmus S.; Savarimuthu, Thiusius R.; Lynggaard, Rasmus B.; Vinholt, Pernille J. (Applied Clinical Informatics, 2023)
Objectives This study evaluated if medical doctors could identify more hemorrhage events during chart review in a clinical setting when assisted by an artificial intelligence (AI) model and medical doctors' perception of using the AI model.Methods To develop the AI model, sentences from 900 electronic health records were labeled as positive or negative for hemorrhage and categorized into one of 12 anatomical locations. The AI model was evaluated on a test cohort consisting of 566 admissions. Using eye-tracking technology, we investigated medical doctors' reading workflow during manual chart review. Moreover, we performed a clinical use study where medical doctors read two admissions with and without AI assistance to evaluate performance when using and perception of using the AI model.Results The AI model had a sensitivity of 93.7% and a specificity of 98.1% on the test cohort. In the use studies, we found that medical doctors missed more than 33% of relevant sentences when doing chart review without AI assistance. Hemorrhage events described in paragraphs were more often overlooked compared with bullet-pointed hemorrhage mentions. With AI-assisted chart review, medical doctors identified 48 and 49 percentage points more hemorrhage events than without assistance in two admissions, and they were generally positive toward using the AI model as a supporting tool.Conclusion Medical doctors identified more hemorrhage events with AI-assisted chart review and they were generally positive toward using the AI model.
Keywords: electronic health records; hemorrhage; artificial intelligence; decision support systems; natural language processing